Hubungan Kecemasan, Fungsi Kognitif dengan Kualitas Tidur pada Lansia di Panti Wreda Jakarta dan Tangerang - Surilena Hasan; Clara Rosa Pujiyogyanti Ajisuksmo; Josephine Retno Widayanti (Jurnal Sains dan Kesehatan, 2025)
Background: Older people living in nursing homes are vulnerable to anxiety, cognitive impairment, and poor sleep quality. This study aimed to examine the association between anxiety, cognitive function, and sleep quality among older people residing in nursing homes in Jakarta and Tangerang. Methods: An analytic cross-sectional study was conducted among 124 residents from seven nursing homes using purposive sampling. Anxiety was assessed using the Generalized Anxiety Disorder-7 (GAD-7), cognitive function using the Indonesian version of the Montreal Cognitive Assessment (MoCA-Ina), and sleep quality using the Pittsburgh Sleep Quality Index (PSQI). Data was analyzed using chi-square tests and odds ratios. Results: Poor sleep quality was observed in 85.48% of participants, cognitive impairment in 83.87%, and anxiety in 29.31%. Anxiety (p = 0.03; OR = 3.46) and cognitive impairment (p = 0.01; OR = 7.15) were significantly associated with poor sleep quality. Conclusion: Anxiety and cognitive impairment are significantly associated with poor sleep quality among elderly nursing home residents.